Testicular metastasis of prostate adenocarcinoma: the other side of orchiepididymitis - Di Rienzo, Gianluca; Tafuni, Alessandro; Maestroni, Umberto; Ruffini, Livia; Silini, Enrico Maria; Gasparro, Donatella; Pilato, Francesco Paolo; Gnetti, Letizia (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2024)
Background. Metastatic prostate adenocarcinoma is a rare event and there are few references to this topic. We report an unusual case of prostate cancer metastasis and review of contemporary literature. Moreover, we discuss the pathogenesis and the clinical aspects of this event. Case presentation. A 70-year-old patient was admitted to the hospital for right scrotal pain. The ultrasound examination described an increase in testicular size, suggesting the possibility of orchiepididymitis. Past medical history reported a previous prostate adenocarcinoma. Inflammatory blood tests were normal. Importantly, PSA was 3.3 ng/ml. PET scan positivity in the scrotum raised suspicion of a relapse. Therefore, he underwent right orchiectomy. Conclusion. Although metastatic prostate adenocarcinoma is rare, a correct diagnosis is of paramount importance because the therapy changes accordingly. Patients who complain of scrotal pain need to be examined accurately. Although the most common cause behind this symptom is infectious, the patient’s past medical history should be reviewed to exclude previous malignancies.